Growing Up American - Nagourney, Peter; Steiner, Susan (Washington, D.C. : Wadsworth Pub., 1972)
This collection represents the record of a summer institute held in 1989 at the College of St. Scholastica in Duluth (Minnesota) in which 40 elementary school teachers and 4 college instructors read and discussed American fiction centering on the theme of initiation/challenge/change. After a beginning section which presents background information, the collection offers the following articles: "Life, Literature and Literary Criticism: Some Reflections" (John P. Schifsky); "Five Answers to a Frowning Question" (Leo J. Hertzel); "Participants' Responses"; "Literature and Ethics in a Sixth Grade Classroom" (Cary Werner); "Confronting Our Beliefs: Literature and Human Experience" (Robert McKeown); and "Teaching Elementary School Children: Some Personal Values" (Jeanne Webb). The collection concludes with a list of the institute participants and an evaluator's report. (SAM)
Includes bibliographical references and index.
Microfiche.
Keywords: Acculturation; Elementary Education; Elementary School Students; Elementary School Teachers; Fiction; Higher Education; Institutes (Training Programs); Language Arts; Literary Criticism; Literary Devices; Reader Response; Summer Programs; Thematic Approach; United States Literature; Collected Works, General